Why Do Big Firms Pay Higher Wages? Evidence from an International Database - Gibson, John; Stillman, Steven (The Review of Economics and Statistics, 2009)
Bigger firms pay higher wages. This note reports tests of the hypothesis that this big-firm premium (BFP) occurs because workers in big firms are more skilled. We use the International Adult Literacy Survey, which gives richer skill measures than those typically available in labor market surveys, to measure the BFP in nine countries with and without controls for worker skill. The results show that the BFP is not as universal as is often suggested, but in countries where it exists controlling for skills does little to reduce the size of the BFP.